2012
DOI: 10.1016/j.jcis.2011.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing N-acetylcysteine (NAC) and N-acetylcysteine amide (NACA) binding for lead poisoning treatment

Abstract: Using antioxidants is an important means of treating lead poisoning. Prior in vivo studies showed marked differences between various chelator antioxidants in their ability to decrease both blood Pb(II) levels and oxidative stress resulting from lead poisoning. The comparative abilities of NAC and NACA to Pb(II) were studied in vitro, for the first time, to examine the role of the –OH/–NH2 functional group in antioxidant binding behavior. To assay the antioxidant-divalent metal interaction, the antioxidants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Recently, it has been revealed that NAC amide (NACA), an NAC derivate with higher bioavailability and enhanced antioxidant properties [8,9], may significantly mitigate the detrimental consequences of various toxic substances in different organs, including the lungs and kidneys [10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been revealed that NAC amide (NACA), an NAC derivate with higher bioavailability and enhanced antioxidant properties [8,9], may significantly mitigate the detrimental consequences of various toxic substances in different organs, including the lungs and kidneys [10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…N-acetylcysteine (NAC) is a thiol (SH) containing antioxidant, which has been investigated for many pathologies treatment, such as liver failure, inflammation, nephropathy and brain disorders [12]. It is a naturally occurring compound found in several vegetables, including garlic, onion [13], peppers and asparagus [14].…”
Section: Introductionmentioning
confidence: 99%
“…The first two, modeled respectively with N-acetylcysteine (NAC) and sodium dodecylbenzenesulphonate (SDBS), both have organic sulfur but in different functional groups (-SH vs -SO 3 ). Moreover, NAC and SDBS have different functional groups and structures: NAC is hydrophilic with additional functional groups (-COOH and -NH 2 ) other than the thiol ligand while SDBS is a linear anionic surfactant with both hydrophilic and hydrophobic (dodecylbenzene) moieties (Chen et al, 2012;Zhai et al, 2004). Although organic sulfide has strong affinity with silver, the sulfur-silver interaction might differ and be specific to the organic molecule containing the sulfur (Levard et al, 2011;Gondikas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%